An Analysis of Fiqh al-Waqi` (An Understanding of Contemporary Problems) on the Ruling of Compulsory Boycott of KFC (Malaysia) - Anas, Mohd Yunus; Wan Mohd Yusof, Wan Chik; Mahani, Mohamad (2013)
The fatwa of compulsory boycott of Israeli goods has been issued by the ruling bodies and scholars. Yet it is often questionable from a practical standpoint and ability of its implementation in the context of the open and global economy especially when involving American products. Among the brands included in the list of businesses to be boycotted is Kentucky Fried Chicken Holding (KFCH) Malaysia, which in fact also involved and contribute to Muslims’ economic and finance in Malaysia. The demand of Islamic law, the practicality of the business world and the reality of the Muslim world should be considered. Hence this paper has been compiled with the aim of analyzing the wise approach of KFCH Malaysia on how to apply the demand of boycotting Israeli and goods. To achieve the objective, this study inductively and deductively analyses information gathered through documents and literature reviews within the framework of Fiqh al-Waqi ' (Fiqh based on reality). The study found that this boycott is not practical in Malaysia and should be evaluated based on factors that would be an advantage or ease and not detrimental or difficult to the Muslim community.